Enrollment Swap Bolster Indigenous Land Property Rights With Bondo Deso (Studies in Sedadi Village Penawangan Subdistrict Grobogan Regency Central Java Province) - Dimas Rizky Wiratama Suwignyo; Yulia Audina Sukmawan; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study to determine: 1) The registration process Swap Bolster Indigenous Land Rights Reserved by Bondo Deso Sedadi Village-Penawangan Subdistrict-Grobogan. 2) Obstacles and How to Overcome It. The approach in this study is a socio legal sourced from primary data and secondary data, qualitative analysis method. Data collection techniques with interviews, and literature. Data were analyzed using qualitative data analysis.Based on the analysis concluded: the alienation of land property rights of indigenous with Bondo Deso form of swaps is based on the public interest to be taken through the initial stages, namely the approval of the Head of Village and BPD (Village Consultation), approval to the Head of the Regional (Regent / Mayor, Governor), the approval of the Minister of Internal Affairs (as related to exchange) and the last is the stage registration right to use the land in the village treasury land Office. The obstacle is that when enrollment in the District Land Office Grobogan occurred facts are different between physical and juridical document, the data from the soil was not a complete history, chronology deed broken or lost and their land disputes and the absence of a line in the measurement of the ground by officers. Therefore, the completion of these problems the government handed it over to PPAT Sedadi village to take care of the land registration. Keywords: Swap Bolster Land; Rights of Indigenous; Bondo Deso